1996
DOI: 10.1021/ic960475k
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Copper(II) Ions in Liquid Ammonia

Abstract: X-ray absorption fine structure (XAFS) measurements have been performed at -50 degrees C on a 0.4 mol dm(-)(3) copper(II) nitrate solution in liquid ammonia. Extended X-ray absorption fine structure (EXAFS) spectroscopy was used to determine the coordination number and bond distances for the solvated copper(II) ion in solution. The equatorial ammonia nitrogens are located 2.00 Å from the copper and the axial nitrogen 2.19 Å from the copper. However, it was not possible from the EXAFS analysis alone to conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
8
25
1
1
Order By: Relevance
“…At the same time, they concluded from the X-ray absorption near-edge structure (XANES) spectrum that the geometry is square pyramidal with five ammonia ligands coordinated to the copper. The results obtained from EXAFS, XANES [9] and X-ray diffraction studies are not consistent with each other. Coordination numbers of four (square planar), [12,13] five (square pyramidal with Cu II lifted above the average nitrogen plane), [14,15] and six (distorted square pyramidal) [16] nitrogen atoms have been reported.…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…At the same time, they concluded from the X-ray absorption near-edge structure (XANES) spectrum that the geometry is square pyramidal with five ammonia ligands coordinated to the copper. The results obtained from EXAFS, XANES [9] and X-ray diffraction studies are not consistent with each other. Coordination numbers of four (square planar), [12,13] five (square pyramidal with Cu II lifted above the average nitrogen plane), [14,15] and six (distorted square pyramidal) [16] nitrogen atoms have been reported.…”
Section: Introductioncontrasting
confidence: 58%
“…The structure of copper II complexes in ammonia has been studied by X-ray absorption fine structure (EXAFS) [9,10] and X-ray diffraction (XRD). [11] The EXAFS results concluded that the Cu II ion was coordinated by five ammonia ligands at equal distances.…”
Section: Introductionmentioning
confidence: 99%
“…The electron beam energy was 1.5-2.2 Gev, and the average beam current was 80 mA. The monochromator consisted of two parallel Si(1 1 1) crystals with an entrance slit of 2 mm (Valli et al, 1996). The XAFS spectra were collected in fluorescence mode using an argon-filled ionization chambers detector at room temperature ($25°C).…”
Section: Collection Of Xafs Datamentioning
confidence: 99%
“…[7][8][9][10] The X-ray absorption spectroscopy (XAS) at the L-edges and the X-ray absorption near edge structure (XANES) at the Kedges for 3d transition metals is a powerful tool for investigating the steric and electronic structures of an absorbing atom center. [11][12][13][14][15][16][17] Since the core-hole lifetime of L-edge transitions is longer than that of K-edges, the L-edge XAS has very narrow inherent linewidths, which lead to better resolved features in the spectra, compared to the K-edge XANES. For Ti K-edge XANES, however, the preedge features in the spectra are very sensitive to the structure surrounding the Ti sites, and provide useful information.…”
Section: Introductionmentioning
confidence: 99%
“…12,16,17,[20][21][22][23][24] So far, nanocrystal TiO2 and Ni ions deposited on a SiO2 crystal have been studied by X-ray absorption experiments. 7,[25][26][27][28] However, TiO2 and Ni ion-doped TiO2 thin films on glasses have been little observed by similar experiments; in addition, the steric and electronic structures of Ti and Ni ions in the thin films on the glasses have not yet been discussed by theoretically analyzing the obtained spectra.…”
Section: Introductionmentioning
confidence: 99%